The Population Problem–Introductory Notes - Leibenstein, Harvey (Quarterly Journal of Economics, 1975)
Journal Article Population: A Symposium: Introductory Notes Get access Harvey Leibenstein Harvey Leibenstein Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 89, Issue 2, May 1975, Pages 230–235, https://doi.org/10.2307/1884427 Published: 01 May 1975